Hubungan Lemak Visceral Dan Tingkat Asupan Gizi Mikro (Natrium,Kalium, Magnesium) Dengan Kejadian Hipertensi di Rumah Sakit Umum Az-Zahra Lampung Tengah: Abstrak, Introduction, Method, Result And Discussion, Conclusions And Suggestions, References. - Nur samsudin, Putri (Journal Aisyah University, 2025)
Hypertension is called the “silent killer”, because this disease is without complaints so that it is only known when the patient has complications. Primary prevention of hypertension to lower blood pressure, among others, is by adjusting the diet. The risk factors that can affect hypertension are visceral fat intake and excessive sodium intake levels can trigger high blood pressure, while potassium and magnesium intake have an effect on lowering blood pressure. This study aims to determine the relationship between visceral fat and the level of micronutrient intake (sodium, potassium, magnesium) with the incidence of hypertension at Az-Zahra General Hospital, Central Lampung. This research design is cross sectional. The sample in the study amounted to 55 respondents taken using purposive sampling technique. The population in this study amounted to 164 patients taken from the last three months of data. This study was conducted from January to February 2025. Visceral fat data were taken using BIA (Bioelectrical Impedance Analysis) and microtoise. Data on micronutrient intake levels (sodium, potassium, magnesium) were obtained through interviews using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Data were analyzed univariately and bivariately using chi square test. The results showed that there was a relationship between visceral fat and the incidence of hypertension with a value of (ρ value = 0.009). There is a relationship between the level of sodium intake and the incidence of hypertension with a value of (ρ value = 0.000). There is a relationship between the level of potassium intake and the incidence of hypertension with a value of (ρ value = 0.001). There is a relationship between the level of magnesium intake and the incidence of hypertension with a value of (ρ value = 0.044). The conclusion of this study is that there is a relationship between visceral fat and the incidence of hypertension and the level of micronutrient intake with hypertension.